2017
DOI: 10.3171/2017.5.focus17245
|View full text |Cite
|
Sign up to set email alerts
|

A neurophysiological approach to nerve transfer to restore upper limb function in cervical spinal cord injury

Abstract: A successful nerve transfer surgery can provide a wealth of benefits to a patient with cervical spinal cord injury. The process of surgical decision making ideally uses all pertinent information to produce the best functional outcome. Reliance on clinical examination and imaging studies alone can miss valuable information on the state of spinal cord health. In this regard, neurophysiological evaluation has the potential to effectively gauge the neurological status of even select pools of anterior horn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…This condition may be ascribed to these evaluation methods are relatively suboptimal to detect subtle difference between different treatments. Similar results were also reported in many previous studies [8,11,[15][16][17], and collateral sprouting induced by longstanding neurodegeneration is likely the main reason. The remarkable increase in MUSIX values in the tested muscles in this study further identi ed the existence of the reinnervation from the surviving motor axons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This condition may be ascribed to these evaluation methods are relatively suboptimal to detect subtle difference between different treatments. Similar results were also reported in many previous studies [8,11,[15][16][17], and collateral sprouting induced by longstanding neurodegeneration is likely the main reason. The remarkable increase in MUSIX values in the tested muscles in this study further identi ed the existence of the reinnervation from the surviving motor axons.…”
Section: Discussionsupporting
confidence: 91%
“…Motor unit number index (MUNIX) is a recently developed quantitative method that provides an estimated index of the number and size of the functional motor units in the tested muscle [8]. According to the previous studies, MUNIX was demonstrated to be very sensitive in detecting motor unit loss in many different neuromuscular diseases [8][9][10][11], and both Li et al and Marciniak et al demonstrated MUNIX detection can be used to assess the integrity of lower motor neuron in patients with SCI [12,13].…”
mentioning
confidence: 99%
“…with cervical SCI, suggesting that peripheral nerve function is compromised following upper motor neuron lesion. Central disconnection of the second-order motor neurons is considered to be the likely reason for this condition, and many previous studies have provided evidence with regard to this disconnection may cause loss of lower motor neurons (LMNs) distal to the initial injury site, which may cause the motor axonal degeneration and an eventual reduction in motor units [1,5,[12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous studies, MUNIX was demonstrated to be very sensitive in detecting motor unit loss in many different neuromuscular diseases [8][9][10][11], and both Li et al and Marciniak et al demonstrated MUNIX detection can be used to assess the integrity of lower motor neuron in patients with SCI [12,13].…”
mentioning
confidence: 99%
“…Central disconnection of the second-order motor neurons is considered to be the likely reason for this condition, and many previous studies have provided evidence with regard to this disconnection may cause loss of lower motor neurons (LMNs) distal to the initial injury site, which may cause the motor axonal degeneration and an eventual reduction in motor units [1,5,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%